2017
DOI: 10.1016/j.bpj.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Organized β-Cell Subpopulations Control Electrical Dynamics across Islets of Langerhans

Abstract: Understanding how heterogeneous cells within a multicellular system interact and affect overall function is difficult without a means of perturbing individual cells or subpopulations. Here we apply optogenetics to understand how subpopulations of β-cells control the overall [Ca] response and insulin secretion dynamics of the islets of Langerhans. We spatiotemporally perturbed electrical activity in β-cells of channelrhodopsin2-expressing islets, mapped the [Ca] response, and correlated this with the cellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
168
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(192 citation statements)
references
References 62 publications
(92 reference statements)
22
168
2
Order By: Relevance
“…62-65 Recent data have demonstrated that highly metabolic cells are more efficient at recruiting neighboring cells. 55 Upon glucose stimulation, GJ coupling between β-cells increases. 66 Furthermore, hub cells express less insulin, 33 and highly GJ coupled cells are known to express less insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62-65 Recent data have demonstrated that highly metabolic cells are more efficient at recruiting neighboring cells. 55 Upon glucose stimulation, GJ coupling between β-cells increases. 66 Furthermore, hub cells express less insulin, 33 and highly GJ coupled cells are known to express less insulin.…”
Section: Discussionmentioning
confidence: 99%
“…55 As hub cells are highly metabolic, 33 this would imply that hub cells may be preferentially connected.…”
Section: Methodsmentioning
confidence: 99%
“…Saturated areas were also removed by limiting the area to intensities below the maximum. To determine if a cell was active, a peak detection algorithm was used to determine if areas of the islet had peak amplitudes greater than 1.5 times the average of quiescent reference cells [32]. A quiescent reference cell (or background region if no cells were quiescent) was chosen manually, and showed no significant fluctuations in intensity during the entire time course.…”
Section: Nad(p)h Imaging-nadh(p)mentioning
confidence: 99%
“…We and others have previously examined how heterogeneity in KATP channel activity and electrical coupling impact overall islet [Ca 2+ ] [9,22,24,26]. However, both single-cell based studies and in-situ analysis have demonstrated that β-cells exhibit substantial heterogeneity in glucose metabolism [27], which includes varying GK expression [21,25,28], metabolic fluxes [29][30][31][32], or mitochondrial function [19,21]. While extensive heterogeneity in glucose metabolism exists within the islet, it is not clear how cell sub-populations with differing GK expression or levels of glucose metabolism influence each other via electrical coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In response to elevated blood glucose concentrations, pancreatic β cells secrete insulin by Ca 2+ -triggered exocytosis. [4][5][6] Although these findings provide important insights into β-cell function, the results are exclusively based either on ex vivo or in vitro data and disregard important factors provided by blood supply, innervation, as well as the metabolic state of islet/β cells under in vivo conditions. 3 A β-cell dysfunction in combination with peripheral insulin resistance is central to the development of type 2 diabetes, a still growing pandemic disease leading to hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%